Non-Contact Thermophysical Property Measurements of High-Temperature Corium Through Aerodynamic Levitation - Yaopeng Gong; Li Zhang; Yidan Yuan; Weimin Ma (Energies)
The thermophysical properties of corium are critical for improving the predictive accuracy of severe accident analysis codes. However, due to the high melting temperature and high volatility of corium, thermophysical property measurements are extremely challenging, resulting in a significant lack of data. This study presents a non-contact measurement facility based on the aerodynamic levitation technique, enabling the measurement of the density, surface tension, and viscosity of corium components at temperatures exceeding 3000 K. Density is measured based on the axisymmetric ellipsoid assumption of levitated drops, while the surface tension and viscosity are determined using the drop oscillation method. Experimental results for key corium components, including ZrO2 and a UO2-ZrO2 mixture, are presented, addressing data gaps in the thermophysical properties of UO2-containing materials.